Psychometric Testing In South Africa: Views from Above and Below - Sehlapelo, Martin; Terre Blanche, Martin (PINS-Psychology in Society, 2026)
Psychometrics played a central role in the development of psychology in South Africa and continues to affect more South Africans than any other branch of psychology. For this reason the transformation of psychology in South Africa will not be complete until psychometric testing practices have been transformed. Interviews with personnel practitioners, political spokespersons, trade unionists, workers and academics, revealed certain convergences and divergences between the views from above and below. Workers tended to have little trust in tests and the testing process, and to see the solution in the formulation of explicit testing policies arrived at through a process of consultation. Personnel practitioners, while acknowledging cultural bias in testing, tended to think that it could be overcome through the construction of non-biased tests. Views from above and below coincided with regard to the popularity of interviewing as an alternative to testing, the idea of learning potential assessment, and the high degree of respect for the technical expertise of psychometricians. This places a heavy burden of responsibility on experts in psychological testing to help redeem psychological testing, and psychology, in the eyes of South Africans.